OPTIMALISASI SUMBER DAYA LOKAL UNTUK MENDUKUNG PROGRAM PEMBELAJARAN INOVATIF DI SMPN3 PAGELARAN - Sugandi, Tatan; Fitriyana, Fitriyana; Rahman, Deni; Mutakin, Asep Zenal; Fauzi, Ikka Kartika Abbas (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
The Community Service Activity “Optimizing Local Resources to Support Innovative Learning Programs at SMPN 3 Pagelaran” aims to integrate local potential into the learning process to improve the quality of education and strengthen students' cultural identity. The methods employed include identifying and mapping local resources, developing an integrated curriculum, teacher training, implementing resource-based learning, and establishing a school-community collaboration network. The results of the activity demonstrate the successful identification of 15 types of natural resources, 8 cultural heritage elements, and 12 local community professions, which were developed into 24 integrated learning modules. The implementation of the program in 36 classrooms increased student active participation from 45% to 87%, student attendance from 78% to 94%, and average test scores from 7.2 to 8.3. 95% of teachers reported increased confidence in local resource-based learning, while 92% of students stated that learning had become more engaging and meaningful. The establishment of the Local Resource-Based Learning Forum created a sustainable learning ecosystem involving all community components and opened opportunities for local economic development.